Registration of ‘Epoch’ hard red winter wheat - Baenziger, P. S.; Frels, K. A.; Boehm, J.; Belamkar, V.; Rose, D. J.; Xu, L.; Wegulo, S. N.; Regassa, T.; Easterly, A. C.; Creech, C. F.; Santra, D. K.; Klein, R. N.; et al. (Journal of plant registrations, 2022)
‘Epoch’ (Reg. no. CV‐1195, PI 699379) hard red winter wheat (Triticum aestivum L.) was developed cooperatively by the Nebraska Agricultural Experiment Station and the USDA‐ARS and released in February 2021 by the developing institutions. It was selected from the cross ‘Hitch’/NW03666. The pedigree of NW03666 is N94S097KS/NE93459. The cross was made in 2009. The F1 generation was grown in Yuma, AZ, in 2010, and the F2 to F3 generations were advanced using the bulk breeding method at Mead, NE, in 2010–2011 to 2011–2012. In 2012–2013, single F3‐derived F4 rows were planted for selection. From 2015 on, Epoch was tested under rainfed or irrigated conditions in single replicate trials with replicated checks (2015) and in replicated alpha lattice trials (2015–2020). There was no further selection in Epoch other than to remove off‐types thereafter. Epoch was selected using both phenotypic and genomic selection for its ability to survive the winter, short stature with strong straw strength, agronomic performance under irrigation, resistance to diseases, and end‐use quality. Epoch seems to be narrowly adapted to irrigated production fields in Nebraska. The name Epoch was chosen because it marks the transition of leadership in the UNL Wheat breeding project from P. Stephen Baenziger to the new wheat breeder, Katherine A. Frels; hence, it marks the end of one era and the beginning of the next. Core Ideas Epoch is a new hard red winter wheat adapted to irrigated production in the central Great Plains. Epoch is not recommended for rainfed production unless the yield potential is similar to irrigated production. Epoch has superior straw strength, winter survival, and good disease resistance. The overall milling and baking aspects of Epoch should be acceptable to the respective industries.